Evaluation of the Combined Treatment Approach “Robin” (Standardized Manual and Smartphone App) for Adolescents at Clinical High Risk for Psychosis - Traber-Walker, Nina; Gerstenberg, Miriam; Metzler, Sibylle; Joris, Maria Raquel; Karr, Markus; Studer, Nadja; Zulauf Logoz, Marina; Roth, Alexander; Rössler, Wulf; Walitza, Susanne; Franscini, Maurizia (Frontiers in Psychiatry, 2019)
The prevention of schizophrenia and other psychotic disorders has led researchers to focus on early identification of individuals at Clinical High Risk (CHR) for psychosis and to treat the at-risk symptoms in the pre-psychotic period. Although at-risk symptoms such as attenuated hallucinations or delusions are common in adolescents and associated with a marked reduction in global functioning, the evidence base of effective interventions for adolescents at CHR state and even ﬁrst-episode psychosis is limited. Thus, the present protocol describes a study design that combines therapy modules for CHR adolescents with a smartphone application supporting the young individuals between the therapy sessions. The treatment approach “Robin” is based on existing therapy strategies for adolescents with first episode of psychosis and the available recommendations for adults with at-risk symptoms. The evaluation aims firstly to compare the efficacy of “Robin” in 30 CHR adolescents aged 14-18 to an active control group (treatment as usual) from a previous study. Primary outcome measures will be at-risk symptomatology, comorbid diagnosis, functioning, self-efficacy and quality of life. For the prospective intervention condition (16 weekly individual sessions + a minimum 4 family sessions), help-seeking adolescents with CHR for psychosis, aged 14-18, will be recruited over three years. At-risk and comorbid symptoms, functioning, self-efficacy and quality of life are monitored at six time points (baseline, during the treatment period, immediately after intervention, and 6, 12, and 24 months later) and compared to the respective measures of the active control group.To the best of our knowledge, this is the first controlled trial to test the efficacy of a specific early psychosis treatment in combination with a smartphone application for adolescents at CHR for developing psychosis. The results of the study are expected to add information that may substantially decrease the burden of CHR adolescents and increase their resilience. It may offer age-adapted and targeted strategies to guide clinicians in the treatment of these vulnerable individuals. Furthermore, research in the field of early intervention will be enriched by our findings.